Post-school education and labour force participation in Canada and Australia - Austen, Siobhan; MacPhail, F. (National Centre for Vocational Education Research, 2010)
This study provides a comparison of the post-school education systems of Australia and Canada using data from the Longitudinal Surveys of Australia Youth and the Canadian Youth in Transition Survey. The results indicate that the Canadian college system is more attractive to high achieving school graduates than is the somewhat comparable Australian VET sector.